Housing, Health, and Happiness - Cattaneo, Matias D.; Galiano, Sebastian; Gertler, Paul J.; Martinez, Sebastian; Titiunik, Rocio (World Bank, Washington, DC, 2012)
Despite the importance of housing for people's well-being, there has been little work done to assess the causal impact of housing and housing improvement programs on health and welfare. In this paper the authors help fill this gap by investigating the impact of a large-scale effort by the Mexican government to replace dirt floors with cement floors on child health and adult happiness. They find that replacing dirt floors with cement floors significantly reduces parasitic infestations in young children, reduces diarrhea, reduces anemia, and improves cognitive development. Finally, they also find that this program leave adults substantially better off, as measured by satisfaction with their housing and quality of life and by their significantly lower rates of depression and perceived stress.